Representações sociais da saúde e políticas de saúde voltadas a populações indígenas : uma análise da relação entre o sistema de saúde guarani e a biomedicina - Bertolani, Marlon Neves (2008)
The Brazilian indigenous movement, from the 1980s on, has definitively set in the national agenda the indigenous right to specific service, which should be able to join health improvement and the respect to cultural diversity. Based on the Theory of Social Representations, the main objective of this research is to identify and to analyze the relationships between two different healthcare systems biomedicne and the Indigenous healthcare system , in the context of actions towards the Guarani indians living in settlements in the outskirts of Aracruz (Espírito Santo, Brazil). It tries to understand how much impact on the actions developed in this área was caused by the social representations that indigenous and health professionals have created regarding the various aspects of this issue, concerning themselves and others , in a scenary marked by inter-ethnical relationships. Because of the complexity of implementing this proposition, which intends to understand actors representations in connection with daily life, an approach envolving a pool of different methodologies for collecting and analysing data has been required: document research, participant observation, semi-structured interview and content analysis. The results have shown the existence of power relationship and fight for hegemony between the subjects linked to the two healthcare systems hereby been analysed. The Guarani representations of health and biomedicine are in accordance with the group s health demands and lead their claims, among which the right to difference is of great importance. Thus, the indigenous experts and leaders have mobilized their available symbolical capital in strategies that aim at preserving the Guarani healthcare system within their own group, gaining this way more control over Occidental agency, as well as more space regarding biomedicine. On the other hand, in the representations expressed by health professionals, the indigenous healthcare system is shown as subordinated and as having a more symbolical than really empirical effectiveness. This attitude is reinforced by the actions put into effect by the Fundação Nacional de Saúde (Health National Foundation), which has ignored the indigenous demands. Besides that, the manner in which health professionals represent the indigenous culture and behavior regarding health and/or the provided services has revealed the perpetuation of an ancient position which is expressed by the envolving society and based on the undestanding of the indigenous by the lack paradigm. This way, the possibilty of understanding them in their concrete positiveness or of perceiving how the other really is get lost. So, what can be said about the Guarani focused in this research is that the recognition of the indian medicine and of theese people s right to their culture, although ratified by the Brazilian State under a formal point of view, has in fact been kept as part of an enormous "alphabet of dead letters".